2014
DOI: 10.1016/j.foodres.2014.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of food matrix and food components on bioaccessibility of pomegranate (Punica granatum) phenolics and anthocyanins using an in-vitro gastrointestinal digestion model

Abstract: Effects of food matrix and individual food components on potential bioaccessibility of pomegranate were investigated by means of simulating in vitro gastrointestinal (GI) digestion. The foodstuffs (sunflower oil, skim milk, cooked lean meat, bread, skim yogurt, probiotic yogurt, apple, lemon, honey, soy milk, cream, and soybean) and the food components (gluten, casein, isolated meat protein, lactose, fructose, galactose, glucose, salt, ascorbic acid, starch, cooked starch, tocopherol, linoleic acid, cellulose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 40 publications
15
65
0
2
Order By: Relevance
“…After simulated intestinal digestion, significantly lower amounts of chlorogenic acid were found compared to simulated gastric digestion (74e85%) (p < 0.05), whereas neither neochlorogenic acid nor caffeic acid was detected. Previous studies also reported dramatic decreases of phenolic acids during in vitro digestion (Celep, Charehsaz, Akyuz, Acar, & Yesilada, 2015;Sengul, Surek, & Nilufer-Erdil, 2014). These reductions in phenolic acids could be associated with changes in pH and the presence of bile salts, which may result in the formation of precipitate (Chethan & Malleshi, 2007).…”
Section: Phenolic Acidsmentioning
confidence: 84%
“…After simulated intestinal digestion, significantly lower amounts of chlorogenic acid were found compared to simulated gastric digestion (74e85%) (p < 0.05), whereas neither neochlorogenic acid nor caffeic acid was detected. Previous studies also reported dramatic decreases of phenolic acids during in vitro digestion (Celep, Charehsaz, Akyuz, Acar, & Yesilada, 2015;Sengul, Surek, & Nilufer-Erdil, 2014). These reductions in phenolic acids could be associated with changes in pH and the presence of bile salts, which may result in the formation of precipitate (Chethan & Malleshi, 2007).…”
Section: Phenolic Acidsmentioning
confidence: 84%
“…Considering our results and the low degree of ellagitannin hydrolysis at pH 3 observed by Tuominen and Sundman (2013), the extra amount of free and glycosylated ellagic acid recovered could be explained by the sum of both: ellagitannins degradation and the release of ellagic acid from the food matrix during in vitro gastric digestion. Accordingly, higher recovery of total phenolic compounds was observed after gastric digestion of pomegranate extract (Sengul, Surek, & Nilufer-Erdil, 2014). In another study, a slight modification in total phenolic content was noticed after the acidic incubation of a wild chokeberry commercial juice (Bermúdez-Soto, Tomás-Barberaán, & García-Conesa, 2007).…”
Section: Stability Of Pomegranate Phenolic Compounds During In Vitro mentioning
confidence: 91%
“…Apple contains an abundance of fibres (de Lima et al, 2014) which hinders the release of phenolic compounds from the fruit pulp, and after pepsin hydrolysation during the gastric digestion, most of the bound phenolic compounds became free and were detected by Folin-Ciocalteu method. exposed to acid conditions (Sengul et al, 2014), meaning the polyphenol compounds could not be detected using the Folin-Ciocalteu method. In addition, Folin-Ciocalteu reagent does not specifically react with phenolic compounds and can also be reduced by other substances including sugars, amines, small peptides hydrolysed by pepsin and organic acid, thus leading to an overestimation of the phenolic content in samples (Oliveira & Pintado, 2015;Mokrani et al, 2016).…”
Section: Tp Content Of Fruit Juices During In Vitro Gi Digestionmentioning
confidence: 99%